Barriers and facilitators to smoking cessation within pregnant Aboriginal and/or Torres Strait Islander women: An integrative review. (June 2019) - Harris, Belinda M.; Harris, Melissa L.; Rae, Kym; Chojenta, Catherine
Highlights: High quality antenatal smoking cessation programs for Indigenous women are lacking. Education for the woman and health professionals may positively impact smoking rates. Involving the partner and family may have a greater impact on the decision to quit. Health professionals need training to provide culturally competent information. Abstract: Objective: To synthesise primary research regarding the facilitators and barriers to smoking cessation amongst Aboriginal and/or Torres Strait Islander women during pregnancy. Design: An integrative review. Review methods: A systematic search of peer-reviewed literature from five databases published from January 2008 to April 2018. Articles were reviewed using the approach outlined by Whittemore and Knafl, with the identified themes collated and synthesised according to study characteristics and barriers and facilitators of smoking cessation. Findings: Of the 310 papers retrieved, nine studies were included within the review (five quantitative and four qualitative). The quality of the studies were ascertained via Joanna Briggs Institute checklists for cross sectional analysis, randomized controlled trials, and qualitative research. The overall quality of the research was deemed acceptable. Two facilitators to smoking cessation within the studied population were identified: 'support to quit' and 'information and advice', while four barriers to smoking cessation within pregnant Aboriginal and/or Torres Strait Islander women were identified: 'smoking prevalence', 'high daily stress', 'ambivalence regarding adverse effects of smoking', and 'attitudes, knowledge and training of the healthcare professional'. Conclusions: Social and familial influences and daily stress have a strong impact on whether a woman feels she can quit smoking during pregnancy. However, in this study, information and advice regarding potential adverse effects of smoking on the foetus, or lack thereof, from health professionals either facilitated cessation of smoking in pregnancy or was a barrier to quitting. Likewise, a lack of awareness from midwives and doctors on smoking cessation strategies, such as nicotine replacement therapy, was a barrier for women. Implications for practice: The findings indicate that education regarding the adverse effects of smoking in pregnancy, as well as strategies on smoking cessation from midwives, doctors, and Aboriginal Health Workers within the antenatal period may have a positive effect on current smoking rates among pregnant Aboriginal and/or Torres Strait Islander women. Involving the partner/support person and family of the woman in this education may have a greater impact on smoking cessation rates through the woman gaining social and familial support in her decision to quit. Thus, healthcare workers require additional professional development to provide information and knowledge within a culturally competent manner. Successful smoking cessation programs for Aboriginal and Torres Strait Islander women during pregnancy could have measurable impacts on mortality rates for Indigenous infants and significantly contribute to 'Closing the Gap'.